Role of the Epstein––Barr virus-encoded latent membrane protein-1, LMP1, in the pathogenesis of nasopharyngeal carcinoma. (August 2009) - Morris, Mhairi A; Dawson, Christopher W; Young, Lawrence S
Although frequently expressed in Epstein––Barr virus (EBV)-positive malignancies, the contribution of the oncogenic latent membrane protein-1 (LMP1) to the pathogenesis of nasopharyngeal carcinoma remains to be fully defined. As a key effector in EBV-driven B-cell transformation in vitro, LMP1 also displays oncogenic properties in rodent fibroblasts, and exhibits similar effects in epithelial cells. LMP1 functions as a viral mimic of the TNFR family member, CD40, engaging a plethora of signaling pathways including: NF-κκB, JNK/p38 (SAPK), PI3-kinase and ERK––MPK. The constitutive activation of these pathways appears central in the ability of LMP1 to induce multiple morphological and phenotypic alterations. Here we review the effects of LMP1 on epithelial cell growth transformation, and its putative role in the pathogenesis of nasopharyngeal carcinoma, focusing on key areas of proliferation, survival, cell motility and invasion.